2011
DOI: 10.1155/2011/982936
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Detection and Recognition of Tonal Bird Sounds in Noisy Environments

Abstract: This paper presents a study of automatic detection and recognition of tonal bird sounds in noisy environments. The detection of spectro-temporal regions containing bird tonal vocalisations is based on exploiting the spectral shape to identify sinusoidal components in the short-time spectrum. The detection method provides tonal-based feature representation that is employed for automatic bird recognition. The recognition system uses Gaussian mixture models to model 165 different bird syllables, produced by 95 bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
34
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 16 publications
1
34
0
Order By: Relevance
“…Typically, the first stage of an automatic system is to parse the acoustic signal into isolated spectro-temporal segments. This is often performed using an energy-based thresholding that requires an estimate of noise level, e.g., [1], or by decomposition into sinusoidal components [1], [2], [3], [4]. A variety of approaches to feature representation of the spectro-temporal segments and their modelling were explored.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Typically, the first stage of an automatic system is to parse the acoustic signal into isolated spectro-temporal segments. This is often performed using an energy-based thresholding that requires an estimate of noise level, e.g., [1], or by decomposition into sinusoidal components [1], [2], [3], [4]. A variety of approaches to feature representation of the spectro-temporal segments and their modelling were explored.…”
Section: Introductionmentioning
confidence: 99%
“…In a case of tonal bird vocalisations, the use of a sinusoidal detection for segmentation also offers a natural way of representing the segment as a temporal sequence of the frequencies of the detected sinusoid, which we refer to as frequency track. This representation was employed in a few earlier studies [1], [6] and also in our recent works [3], [4], [7], [8], [9], [10]. Among the acoustic modelling approaches, the most commonly used are Gaussian mixture models (GMM) [1], [3], hidden Markov models (HMMs) [1], [4], [6], [11], and decision trees [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In exception of most of the published work, in [17] waterfall noise was added to bird recordings and it was shown that the recognition of bird sounds in noisy conditions reduces significantly the recognition performance. In this article, we evaluate several different machine learning algorith ms on the task of bird species classificat ion in real-field conditions, under the concept of AMIBIO project (LIFE08-NAT-GR-000539: Automatic Acoustic Monitoring and Inventorying of Biodiversity, Project web-site: http://www.amibio-project.eu/).…”
Section: Introductionmentioning
confidence: 99%
“…Different parametric representations for the bird vocalizations audio signals have been used, among which Mel frequency cepstral coefficients [5,6,16,17] are the most widely used. Other audio features which have been proposed in the literature are the linear predictive coding [16], linear p redictive cepstral coefficients [16], spectral and temporal audio descriptors [12], and tonal-based features [17].…”
Section: Introductionmentioning
confidence: 99%